A case study of the use of ICT tools and software in teaching among visual art teachers in a Malaysian primary school / Mohd Azwan Anuar - Anuar, Mohd Azwan (2013)
Nowadays, Information and Communication Technology (ICT) has become a challenge to the nation, particularly to the education system to provide human resources with knowledge and expertise in this field. Three main objectives of this case study are to investigate how teachers use ICT tools in the process of teaching and learning Visual Arts in Primary School; to investigate the factors that influence teachers in using ICT in teaching and learning Visual Arts in Primary School; and to investigate the teachers’ understanding of the use of ICT tools and software in teaching and learning Visual Arts in the primary school. The method used is a mixed method design based on a case study. Activities such as interview, observation and survey were used to collect data. For the interviews, observations and survey, the researcher collected and retrieved information from teachers involved, where the emphasis was on the problems faced by teachers in the use of ICT in teaching and learning of Visual Arts. It was found that the problems that existed among the teachers in the use of ICT tools and software technology in the teaching of Visual Arts in the school were problems related to time, the attitude of teachers, lack of knowledge and skills, inadequate exposure and training in ICT, lack of computer labs in the school and imperfect ICT facilities. Finally, suggestions are given relating to the use of techniques (Instruction Manual) for Paint software to be used by teachers in the teaching of Visual Arts at the school.